2015
DOI: 10.1128/iai.03056-14
|View full text |Cite
|
Sign up to set email alerts
|

The Cpx System Regulates Virulence Gene Expression in Vibrio cholerae

Abstract: Bacteria possess signal transduction pathways capable of sensing and responding to a wide variety of signals. The Cpx envelope stress response, composed of the sensor histidine kinase CpxA and the response regulator CpxR, senses and mediates adaptation to insults to the bacterial envelope. The Cpx response has been implicated in the regulation of a number of envelope-localized virulence determinants across bacterial species. Here, we show that activation of the Cpx pathway in Vibrio cholerae El Tor strain C670… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 101 publications
0
19
0
Order By: Relevance
“…As such, the enrichment of TCSs among the identified regulatory genes suggests that the loss of RND efflux may have resulted in physiological alterations in the periplasmic compartment; perhaps due to the accumulation of substrates that are normally effluxed from the periplasm by the RND systems. Several of the identified TCSs contribute to environmental adaptation and pathogenesis including CpxRA [ 16 18 ], CarRS [ 19 , 20 ], VieSAB [ 21 ], and OmpR [ 22 ]. We excluded several of the identified genes as virulence regulators in JB485 including cpxRA , vexR , and breR as previous studies suggested that they did not affect CT and TCP production [ 18 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…As such, the enrichment of TCSs among the identified regulatory genes suggests that the loss of RND efflux may have resulted in physiological alterations in the periplasmic compartment; perhaps due to the accumulation of substrates that are normally effluxed from the periplasm by the RND systems. Several of the identified TCSs contribute to environmental adaptation and pathogenesis including CpxRA [ 16 18 ], CarRS [ 19 , 20 ], VieSAB [ 21 ], and OmpR [ 22 ]. We excluded several of the identified genes as virulence regulators in JB485 including cpxRA , vexR , and breR as previous studies suggested that they did not affect CT and TCP production [ 18 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Experimental evidence in Escherichia coli then provided a model: when misfolded envelope proteins accumulate, CpxA autophosphorylates and then transfers the phosphate group to CpxR, which causes the upregulation of a series of chaperonins and proteases that can degrade or refold the misfolded proteins, thus alleviating the envelope stress (Vogt and Raivio, 2012 ). In recent years, the CpxA/CpxR system has been demonstrated to be involved in the virulence of uropathogenic Escherichia coli (Debnath et al, 2013 ), Salmonella enterica serotype Typhimurium (Humphreys et al, 2004 ), and Vibro cholerae (Acosta et al, 2015 ). The CpxA/CpxR system has also been shown to be involved in the biofilm formation of E. coli (Dorel et al, 1999 ; Ma and Wood, 2009 ; Dudin et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Haemophilus ducreyi , the CpxRA TCS seems to control the expression of many genes, including several major virulence determinants (Labandeira‐Rey et al ., ; Gangaiah et al ., ). In Vibrio cholera , the CpxRA TCS was shown to be involved in envelope stress response and adaptation to low iron, and was recently shown to control the expression of virulence genes (Acosta et al ., ,b). In Yersinia pseudotuberculosis the CpxRA TCS has been shown to influence the contact of Yersinia with eukaryotic cells (Carlsson et al ., ; Liu et al ., ) and like in E. coli the conserved aspartic acid in the Yersinia CpxR receiver domain was shown to be critical for its function and self‐interaction (Ronnebaumer et al ., ; Thanikkal et al ., ).…”
Section: Introductionmentioning
confidence: 99%